EVALUATION OF THE POULTRY INDUSTRY BUSINESS USING SWOT AND PESTEL ANALYSIS - Anggraini, Novita Dwi; Khalid, Zulvia (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study examines the business of Ingham's Group Limited, a major player in Australia's poultry industry, using SWOT and PESTEL analysis. The SWOT analysis reveals Ingham's strengths including a strong industry reputation and diverse product range. However, weaknesses include reliance on domestic markets and high production costs. Opportunities include growing demand for healthy products, foreign market development, and product innovation. Threats include intense competition and changing raw material costs. Political factors, such as international trade policies and health and food safety laws, significantly impact the company's operations. Economic factors, such as foreign exchange rates and global economic conditions, also influence financial success. Social factors, such as consumer preferences for healthier products and demographic changes, also influence demand. Technological considerations include automation technology and product development. Legal considerations, including animal welfare, health and safety, and environmental legislation, also impact the company's business plan. Strategic recommendations include product diversification, market expansion, operational efficiency, branding, and sustainability commitment.